A novel neck brace to characterize neck mobility impairments following neck dissection in head and neck cancer patients - Biing-Chwen Chang; Haohan Zhang; Sallie Long; Adetokunbo Obayemi; Scott H. Troob; Sunil K. Agrawal (Wearable Technologies, 2021)
Abstract